Flipbook "Sexual Harassment" as a Digital-Based Counseling Service Media for Elementary School Children - Jamain, Ririanti Rachmayanie; Sulistiyana, Sulistiyana; Putro, Hendro Yulius Suryo; Arsyad, Muhammad; Isma, Isma; Ramadhan, Muhamad Rico (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
Education in Indonesia faces significant challenges related to three major issues known as the "three great sins of education," namely bullying, sexual violence, and intolerance. This article discusses the importance of sex education and sexual harassment prevention among students, particularly at the elementary school level. Through training with stages of planning, implementation, and evaluation in the form of a post-test questionnaire involving nine guidance and counselling teachers at SD IT Ukhuwah Banjarmasin, brainstorming methods and direct practice were applied to enhance understanding of sexual harassment and teachers' abilities to create digital-based service media, such as flipbooks. The training results showed an increase in participants' knowledge about sexual harassment issues and their ability to use flipbooks as a tool in counselling services. By utilizing technology, it is hoped that the younger generation can better understand and prevent sexual harassment actions, as well as create a safer and more supportive learning environment.